Desenvolvimento de novos aços inoxidáveis lean - propriedades mecânicas e tribológicas - Silva, Rinara Gregório (Universidade Federal de São Carlos, 2024)
Carbon steels are attractive materials given their low cost and satisfactory mechanical strength for various engineering applications. The low price of carbon steel is ascribed to the reduced content of alloying elements, such as Cr, but with the expense of the corrosion resistance. Stainless steels, in turn, combine high mechanical and corrosion resistances, this latter assured by the higher Cr levels, normally above 10.5 wt%. A large compositional region of steels containing Cr in the range between 6 and 11 wt% is still little explored. These Cr-lean steels promise as competitive alternatives for applications in presence of aqueous medium, whose aggressiveness is low for traditional stainless steels, but high for carbon steels. Thus, this project aims to produce and to evaluate the mechanical and wear resistances of steels with low carbon content (< 200 ppm) and chromium varying between 6 and 11%. The steels were produced in a vacuum induction furnace at the Materials Engineering Department at UFSCar and rolled, annealed, and pickled at Aperam, in Timóteo – MG. The alloys were characterized in terms of chemical composition, microstructure and mechanical properties in tensile tests. Wear resistance under annealed and tempered conditions was assessed through the microsclerometry and dry sand in a rubber wheel. The results showed that the mechanical strength increases with the increase of the chromium content for the annealed condition. On the other hand, in the quenched condition similar properties for all alloys was observed regardless of the Cr content, ~1GPa of tensile strength and a hardness of ~270 HV. The abrasive wear tests showed that the quenched condition has higher resistance, and the predominant wear mechanism was micro-grooving. From this work results we conclude that the martensitic microstructure is not so fragile, it is strong, hard, more resistant to abrasive wear and we can remove the chromium while maintaining the same mechanical strength level for lean alloys.
Development of new lean stainless steels - mechanical and tribological properties
Keywords: Aço inoxidável; Desgaste; Tribologia; Propriedades mecânicas; Stainless steel; Wear; Tribology; Mechanical properties; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA; 9. Indústria, Inovação e Infraestrutura